PENATAAN DAN PENGEMBANGAN RUANG KORIDOR SUNGAI CI TARUM BERLANDASKAN KEARIFAN DAN ASPIRASI MASYARAKAT LOKAL - Rohmat, Dede; Sugito, Nanin Trianawati; Ridwana, Riki; Malik, Yakub; Ihsan, Muhammad; Putri, Indri Megantara; Wijaya, Muhamad Akbar; Sudrajat, Daffa Rizal Fauzan; Hakiki, Fikri Nurwan (Jurnal Pendidikan Geografi Gea, 2024)
Ci Tarum River is one of the rivers that is widely used for people's lives. Over time, the environmental conditions of the Ci Tarum River have decreased in quality. Ci Tarum has at least five segments with its own characteristics and focus on problems in each segment. Problems commonly encountered along the Ci Tarum stream are caused by land use along the riverbank, characteristics of residents around the river, characteristics and morphology of land around the river, land ownership status and policies and law enforcement. The handling of problems that occur in the river corridor has been implemented in one of the rivers in Melbourne, Australia, namely the Yarra River. There are several things that need to be considered in handling problems in the Ci Tarum River, namely the actual condition and use of land in the river corridor, land tenure status and social control, potential pollutants in the form of liquid and solid waste, community aspirations in the study village as well as pre-design development and utilization development. land in the Ci Tarum River Corridor. The urgency to organize the Ci Tarum River corridors from a physical and social perspective is important to balance or make as proportional as possible.